Jack's little party - Graham, Bob (London : Walker Books, 2007)
"Jack's mum isn't like other mums at the school gate, and sometimes he feels embarrassed. But when his friend Sam comes home with them for Jack's birthday party, Jack realizes that different is fun!"--Cover.
Keywords: Birthday parties -- Juvenile fiction; Fiction